The Impact of Brand Image and Customer Commitment on Loyalty: An Empirical Study of Automobile Sector - Yu-TeTu, Yu-TeTu; ., Tan-Kui Hsu (Information Management and Business Review, 2013)
Corporate brand image has been assessed as an important antecedent of customer commitment and loyalty. Corporate brands help companies achieving higher performance, such as sales. A poor brand image will lead to disaster, and lose customers. Marketing exists to deliver more value to satisfy customers as well as build a long-term and mutually profitability relationship with customers. If a firm’s products or services do not satisfy or meet the customer’s needs and wants, all the strategies are insufficient. With loyal customers, companies can have higher market share and reduce the operating cost. This initial study was from relevant literature, then set up research structure and hypotheses. Survey was employed, and respondents were collected from automobile sector in Taiwan. There were 170 usable questionnaires to analyze normality, convergent and discriminant validities, and SEM model by PASW 18 and AMOS 18.0. The research found that corporate brand image significantly affects customer commitment and loyalty, and customer commitment has strong impact on customer loyalty for the sample. Therefore, firms need to specifically focus on a long-term and mutually profitability relationship with a customer and create loyalty as competitive advantages in the markets.